Antisemitism Explained - Baum, Steven; Samuels, Shimon (Lanham : University Press of America, 2011)
In this book, Baum carefully guides the reader through the social mind and explains how the formation of social beliefs can be used as a narrative to determine reality. He offers a new perspective regarding how antisemitic legends and folk beliefs form the basis of our ongoing social narrative.
Illustrations; Foreword; Preface; Acknowledgments; Introduction; Chapter One. Breakfast, UFOs, and the Social Mind; Chapter Two. The Jew as Legend; Chapter Three. Principles of Advertising; Chapter Four. Society's Voice; Chapter Five. Israel--The Imaginary Jew in Collective; Chapter Six. The Future of a Delusion; Postscript; Appendix; Bibliography; Index; About the Author.
Description based on print version record.
Keywords: Antisemitism -- Germany -- History; Antisemitism -- Germany; Holocaust, Jewish (1939-1945) -- Personal narratives; Psychology; History; Antisemitism -- Germany -- History; Antisemitism -- Germany; Holocaust, Jewish (1939-1945) -- Personal narratives; PSYCHOLOGY / Reference; Electronic books